Presto Milkfish Processing Training to increase the Selling Value of Milkfish in East Kutai - Heriyati, Eny; Prihatiningsih, Endang; Jainuddin, Jainuddin; Gunarti Ningrum, Tri (Universitas Muhammadiyah Palembang, 2022)
The purpose of this training activity is to carry out one of the Three Pillars of Higher Education, namely Community Service, fostering social awareness in the community, and fostering insight into creating a milkfish processing business for the Family Welfare Empowerment Group, North Sangata District, East Kutai Regency. The implementation of this activity consists of counseling and the practice of presto milkfish processing, as well as an analysis of micro business income. Armed with skills in processing presto milkfish is expected to be used as a micro business in order to increase family income. Milkfish presto processing was chosen as one of the micro business efforts, because this type of fish is quite abundant in East Kutai Regency. However, some people are reluctant to consume milkfish because the meat has quite a lot of fine thorns. To overcome this, presto milkfish processing can be an option for processing which is expected to increase the selling value of milkfish. The target of this community service activity is to help the community in entrepreneurship in producing presto milkfish and to be able to calculate the profits.